Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species - Costa, Wilson J. E. M. (Zootaxa, 2007)
The seasonal plesiolebiasine killifish genera Pituna Costa, Plesiolebias Costa, and Maratecoara Costa, endemic to central and northeastern Brazil, are revised. A key is provided for the identification of plesiolebiasine genera, and keys are also included for species of the three revised genera. Six species are recognized in Pituna: P. brevirostrata n. sp. from the rio Paranaíba drainage, rio Paraná basin; P. poranga Costa from the rio Araguaia basin; P. compacta Myers from the rio Tocantins basin; P. schindleri n. sp. from the rio Parnaíba basin; P. obliquoseriata n. sp. from the rio das Mortes drainage; and P. xinguensis Costa & Nielsen n. sp. from the rio Xingu basin. Four new species of Plesiolebias are described, complementing a recent revision of the genus (Costa, 1998c): P. fragilis n. sp., from the middle rio Araguaia basin; P. altamira Costa & Nielsen n. sp., from the rio Xingu basin; P. filamentosus Costa & Brasil n. sp., from the rio Tocantins floodplains; and P. canabravensis Costa & Nielsen n. sp., from the rio Canabrava floodplains, rio Tocantins basin. Three species are recognized in Maratecoara: M. lacortei (Lazara), from the Araguaia–das Mortes basin; M. formosa Costa & Brasil, from the middle rio Tocantins floodplains; and M. splendida n. sp. from the rio Canabrava floodplains, rio Tocantins basin.